FINANCIAL MARKET DEVELOPMENT AND ECONOMIC GROWTH: EXAMINING HOW THE DEVELOPMENT OF FINANCIAL MARKETS, INCLUDING STOCK MARKETS AND BOND MARKETS, INFLUENCES ECONOMIC GROWTH AND INVESTMENT IN THE EMERGING MARKET - Ahmed Olatunji, A. (Scholar Express Journals, 2023)
This study delves into the intricate relationship between financial market development and economic growth, focusing on the evolution of financial markets, including stock markets and bond markets. The Least Squares approach is used to assess the study's data, which cover the years 1980 through 2022. The findings of this research demonstrate a distinct causal link between Nigeria's economic growth and the expansion of the banking industry. The research also demonstrates the development of Nigeria's financial market's considerable and statistically significant favorable influence on the country's economic expansion. The research's conclusions shed light on the mechanisms regulating the development of the financial market in light of the expansion of the country's economy throughout the study period. The research uses market capitalization, total stock traded, and domestic share as proxies for financial market development and emphasizes the significant beneficial effects of these parameters on GDP. These results highlight how crucial a robust banking sector is to fostering economic growth. This information is necessary for stakeholders and policymakers to develop specific policies that support the development of a sustainable economy and a welcoming financial market environment. To better understand and improve the development of financial sector policy, future study should delve further into the complex connection between these financial parameters and GDP
Keywords: Financial Market Development; Economic Growth; Banking Industry